2022
DOI: 10.3390/jcm11216362
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variants of the PDGFRB Gene Influence Efficacy of PRP Therapy in Treating Tennis Elbow: A Prospective Cohort Study

Abstract: Background: Differences in response to PRP (platelet-rich plasma) therapy may be linked to the variability of growth factors and their receptor’s genes. Considering that, we checked whether the platelet-derived growth factor receptor beta gene (PDGFRB) single nucleotide polymorphisms (SNPs) affect the effectiveness of PRP therapy in treating tennis elbow patients. Methods: The treatment efficacy was analyzed over time (2, 4, 8, 12, 24, 52, and 104 weeks after PRP injection) on 107 patients (132 elbows) using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In recent decades, the use of PRP has gained popularity in the field of tissue engineering because of its anti-inflammatory and analgesic properties, as well as its capacity to induce neo-angiogenesis, tissue formation, and remodeling by influencing stem-cell migration, proliferation, and differentiation [ 14 ]. Because of these properties, the clinical use of PRP in the orthopedic field has increased more and more, with it finding an application with encouraging results in the most common orthopedic pathologies, such as muscle lesions, acute and chronic tendinitis, mild osteoarthritis, and osteochondral lesions [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the use of PRP has gained popularity in the field of tissue engineering because of its anti-inflammatory and analgesic properties, as well as its capacity to induce neo-angiogenesis, tissue formation, and remodeling by influencing stem-cell migration, proliferation, and differentiation [ 14 ]. Because of these properties, the clinical use of PRP in the orthopedic field has increased more and more, with it finding an application with encouraging results in the most common orthopedic pathologies, such as muscle lesions, acute and chronic tendinitis, mild osteoarthritis, and osteochondral lesions [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of all these characteristics, PRP has found wide application in clinical practice, useable as local infiltration in many orthopedic diseases, such as as mild osteoarthritis, acute and chronic tendinitis, and plantar fasciitis, as well as in pathologies that are not strictly orthopedic, such as the treatment of chronic wounds and diabetic ulcers, and it has even found application in other fields of medicine, such as plastic surgery and medical esthetics [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms were also investigated as possible factors for various responses of patients in the tissue healing process. Researchers Szyluk et al demonstrated that polymorphic variants of PDGFRB gene, which encodes the PDGFRB receptor involved in the development of blood vessels and in the bone healing process, influence the effectiveness of PVRP treatment of tennis elbow [ 68 ].…”
Section: Composition Of Plasma Rich With Platelets and Extracellular ...mentioning
confidence: 99%
“…Numerous papers prove the wide application of PRP in tissue regeneration in various fields, such as dentistry, orthopedics, maxillofacial surgery, sports medicine, ophthalmology, and peripheral nerve regeneration. Currently, the most extensive research is being conducted on the use of PRP for tissue regeneration and repair and the prevention of infection [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%